Early and stable difficulties of everyday executive functions predict autism symptoms and emotional/behavioral problems in preschool age children with autism: a 2-year longitudinal study - Lupi, Elisabetta; Tucci, Federico; Casula, Laura; Novello, Roberta Lucia; Guerrera, Silvia; Vicari, Stefano; Valeri, Giovanni (Frontiers in Psychology, 2023)
Longitudinal studies of autistic children show that autism symptoms and emotional/behavioral problems vary and change over time. However, the factors that affect this variability remain far from certain and very little is known about what take place in the preschool period and the role of Executive Functions (EF). Here, we test the influence of stable difficulties in Everyday Executive Functioning (EEF) during early childhood across two years on autistic symptoms and emotional and behavioral problems. Twenty-nine autistic children (24 males and 5 females) were assessed twice within the space of 2 years. At Baseline (M =29 months, SD =5.6 months), participants were assessed with EEF, cognitive development, autistic symptoms and emotional/behavioral problems. At Follow up, we repeated the same assessment except for cognitive development. The group with stable difficulties (across two years) in EEF during early childhood showed a worsening in the severity of autistic symptoms and emotional and behavioral problems if compared with children without EEF difficulties (p<0.05), and these effects cannot be attributable to cognitive development. These short-term longitudinal and preliminary findings underscore the importance of EEF as necessary target for early intervention in children with ASD.